The impact of text availability on task-demands understanding and question-answering in multiple-document reading - Giménez-Salvador, Mariola; Cerdán, Raquel; Rouet, Jean-François (Frontiers in Education, 2025)
In this study, we examined how first-year undergraduates understood and represented a set of questions that they were asked to answer based on three texts about advertising. Our main goal was to capture this process of task-demands understanding (i.e., task-model construction) and its impact on performance in a multiple-document reading context, with or without access to the texts. Fifty students read three complementary texts on advertising and answered ten comprehension questions. Additionally, they were asked to solve a question-demands assessment by indicating which paraphrase, among three options, better reflected each question’s meaning. Participants with text availability were more successful in question-demands understanding, question-answering performance, and included fewer mistakes in their answers. Moreover, text availability moderated the relationship between question-demands understanding and question-answering performance.